Connection Leadership Serve To Behavior OCB With Employee Empowerment And Supervisor-Subordinate Interaction As Mediator As Well Gender As Moderator - Feri Hardiyanto; A.A Alit Merthayasa; Amelia Amelia (Publikasi Indonesia, 2024)
Examine the objective of evaluating the influence of servant leadership on organizational citizenship behavior (OCB) with a focus on worker empowerment and superior-subordinate interactions as potential mediators. This study, conducted at PT XYZ, employed analytical techniques such as the absolute difference method, t-test for independent samples, and Baron & Kenny's causal step method to assess the hypotheses. The population and sample comprised 113 outsourced employees at PT XYZ 1, utilizing a fed-up sampling technique. The findings of the research indicate that servant leadership does not exert a significant impact on OCB when gender serves as a moderator. In this research model, gender does not function as a moderating variable. Both male and female outsourced employees share a positive perception of servant leadership within the company, resulting in similar OCB behaviors between the two groups. The presence of the servant leadership variable alone is adequate as an antecedent for fostering positive OCB in employees, irrespective of their gender characteristics. Furthermore, servant leadership significantly influences OCB through the mediation of worker empowerment and superior-subordinate interactions. Leaders who embody characteristics such as love, empowerment, vision, and humility effectively empower workers and foster positive interactions between superiors and subordinates, thereby contributing to OCB behaviors beneficial for the organization.